Role of 2‐Dimensional Ultrasound Imaging in Placental and Umbilical Cord Morphometry: Literature and Pictorial Review. (29th May 2019) - Ismail, Khadijah I.; Hannigan, Ailish; O'Donoghue, Keelin; Cotter, Amanda
Abstract : Abnormalities of the placenta and umbilical cord have been associated with adverse pregnancy outcomes. Antenatal detection of placental and umbilical cord abnormalities using ultrasound (US) imaging is now gaining popularity with the advancements in obstetric US. This article reviews the use of 2‐dimensional obstetric US as a tool to measure and assess placental and umbilical cord morphometry. It highlights the potential role of placental and umbilical cord morphometry as a valuable component of the screening tool for high risk pregnancies and identifies the need for further research to examine its feasibility.